Effect of Temperature and Pre-stressed Voltage on Breakdown of Oil-Impregnated Paper - Cui, H.; Yang, L.; Li, S.; Abu-Siada, Ahmed; Yan, W.; Qu, G.; Li, S.; Zhu, Y.; Yue, W. (2018)
© 2018 IEEE. With the rapidly increasing demand for electric power in society, power transformers are expected to exhibit more stresses that accelerate the process of insulation system degradation. However, the effect of temperature and pre-stressed voltage on breakdown of oil immersed paper degradations is still not being fully revealed. In this paper, the electrical degradation of mineral oil impregnated kraft paper has been discovered under variable temperature and the divergent time of varying prestressed voltage. Besides, due to mineral oil-based insulation system of power transformers may contaminate soil after occasional leakage though unsealed seam, the relevant properties of an environmental friendly insulating oil, FR3 fluid is compared with mineral oil. The DC breakdown voltages of mineral oil-paper and FR3 fluid papers respectively decrease by 21 % and 12% with the increase of the oil temperature. The AC breakdown voltage of these two oil-papers does not change significantly with the varying temperature. Besides, the breakdown property of these two oil-papers change significantly with the time of pre-stressed voltage. Finally, considering the insulation performance, heat dissipation performance and sustainable development performance of FR3 and mineral oil-impregnated paper, FR3 fluid is a promising dielectric fluid to replace mineral oil under its application in low voltage level.